2002
DOI: 10.1038/sj.onc.1205930
|View full text |Cite
|
Sign up to set email alerts
|

Proviral activation of the tumor suppressor E2a contributes to T cell lymphomagenesis in EμMyc transgenic mice

Abstract: The basic helix -loop -helix factor E2A plays an important role in the development of B and T lymphocytes. In addition, E2a has been implicated as a gene with tumor suppressor activity, since mice deficient for E2a succumb to T cell lymphomas. We have performed retroviral tagging in EmMyc transgenic mice to identify genes that contribute to lymphomagenesis. The EmMyc transgenic mouse is a well-established model of a common translocation in human B cell lymphomas. Analyses of the proviral insertion sites in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
(59 reference statements)
0
11
1
Order By: Relevance
“…Two recent studies using retroviral tagging identified the locus Sox4, encoding a transcription factor involved in B-and T-cell development, as a CIS for Moloney MuLV (25,31). Although Sox4 was the most frequently targeted CIS in the study by Suzuki et al (31) (55 of 194 tumors), we were unable to detect any TBLV integrations near Sox4.…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…Two recent studies using retroviral tagging identified the locus Sox4, encoding a transcription factor involved in B-and T-cell development, as a CIS for Moloney MuLV (25,31). Although Sox4 was the most frequently targeted CIS in the study by Suzuki et al (31) (55 of 194 tumors), we were unable to detect any TBLV integrations near Sox4.…”
contrasting
confidence: 49%
“…Complementarity between these two genes was suggested by Winoto and Littman (35) and indicates the utility of using numerous genetic and viral models to examine oncogenic pathways since other large-scale retroviral tagging studies using MuLV failed to detect the Ror␥ locus as a CIS (19,25). Furthermore, 8.5% of the TBLVinduced tumors showed integrations in both c-myc and Ror␥ (Table 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, newly developed PCR technologies and the mouse genome sequence databases allowed efficient high-throughput screening for retrovirally tagged genes. A large number of common insertion sites (CIS) in Moloney murine leukemia virus (M-MuLV)-induced lymphomas have recently been reported (Hwang et al, 2002;Lund et al, 2002;Mikkers et al, 2002a;Suzuki et al, 2002), highlighting the power of retroviral insertional mutagenesis. These developments urged us to start an exhaustive screening for novel oncogenes in MMTV-induced mouse mammary tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Although Tal1 cannot form homodimers, it interacts and inhibits other helix-loop-helix factors such as E47/E2A and HEB (1,3). E47/E2A has been implicated as a gene with tumor suppressor activity because mice deficient for E2A succumb to T-cell lymphomas (4). A recent report showed that Tal1 induces T-ALL primarily by inhibiting transcriptional activity of E47 (3).…”
Section: Introductionmentioning
confidence: 99%